The productivity tax of new office concepts: a comparative review of open-plan offices, activity-based working, and single-office concepts - Andrea Gerlitz; Marcel Hülsbeck (Management Review Quarterly, 2023)
This systematic review critically analyzes the relationship between office concepts and individual and organizational performance. Based on the current literature, we identify seven key dimensions to guide our understanding: office concept, work, personality fit, satisfaction, health, control paradigm, and enabling paradigm. Our systematic search yielded 429 published papers on office concepts and performance between 2005 and 2022. Rigorous selection criteria narrowed them down to 46 empirical articles included in this analysis. The results show that activity-based working not only negatively impacts performance but also affects employee satisfaction and health. Open-plan offices can reduce real-estate costs but lead to lower performance levels, thereby imposing a tax on productivity which outweighs the initial cost savings. Activity-based working has the potential to enhance collaboration and interaction but is dependent on a professional and proactive management. In most cases, especially for knowledge workers, the single office turns out to be the environment in which employees show the best individual and organizational performance.
Keywords: 650; Productivity tax; Employee; Satisfaction; Performance; Office concept; Open-plan office; Activity-based working; Single office